An efficient far‐red emission Sr2InSbO6:Mn4+, M (M = Li+, Na+, and K+) phosphors for plant cultivation LEDs. Issue 2 (21st September 2021) - Xie, Yan; Geng, Xue; Wang, Yuan; Guo, Jiang; Lu, Yuhui; Lv, Qiuyi; Ma, Zhijiang; zhang, Dan; Zhao, Jin; Deng, Bin; Yu, Ruijin
Abstract: High‐efficiency and far‐red light phosphors based on Mn 4+ ‐doped inorganic luminescence materials are beneficial to plant cultivation. However, Mn 4+ ‐doped oxide phosphors have a common problem of low quantum efficiency. Alkali metal ion codoping can effectively improve the luminescence properties of Mn 4+ ‐activated oxide phosphors. Herein, a series of Sr2 InSbO6 :Mn 4+, M (SISO:Mn 4+, M) (M = Li +, Na +, and K + ) far‐red‐emitting phosphors codoped alkali metal ions were first synthesized. Density functional theory calculation indicated that SISO is a kind of indirect bandgap material with a bandgap of ∼1.60 eV. The SISO:Mn 4+ samples showed a far‐red light at 698 nm upon 365 nm, which perfectly matched the absorption spectrum of the far‐red‐phytochrome (Pfr) of plants. The doping concentration of the SISO:Mn 4+ samples was optimized to be 0.006 mol. The concentration quenching mechanism was defined as dipole–dipole interaction by combining the Dexter theory and the Inokuti–Hirayama model. Optimizing the sintering temperature and codoped with alkali metal ions (Li +, Na +, and K + ) could improve the luminescent intensity of SISO:Mn 4+ . The optimum sintering temperature was 1300°C. The internal quantum efficiencies of SISO:0.006Mn 4+ and SISO:0.006Mn 4+, 0.006Li + phosphors are 22.67% and 60.56%, respectively. SISO:Mn 4+, Li + phosphors‐based plant growth light‐emitting diodes (LEDs) demonstrate excellent optical stability and long lifetime. Thus, these phosphors are promising candidates for plant cultivation LEDs.